Celebrity Endorsement, Viral Marketing, And Halal Labelling Effect On Gen Z Skincare Camille Beauty Purchasing Decisions - Aulia Vivi Firdasari; Rizky Eka Febriansah; Alshaf Pebrianggara (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the influence of celebrity endorsements, viral marketing, and halal labels on Gen Z consumers' purchasing decisions regarding Camille Beauty Skincare. Methodology: A descriptive quantitative research design was used, utilizing a purposive sampling technique with 100 respondents. Data were analyzed using SmartPLS software, including Outer Model Test analysis, Cronbach's Alpha, Average Variance Extracted (AVE), Composite Reliability, R², and path coefficient estimates. Results: The study shows that celebrity endorsement has a negative effect on purchasing decisions (T= 0.257 p = 0.797), Viral Marketing shows a positive effect on purchasing decisions (T= 6.903, p = 0.000) and Halal Labeling has a negative effect on purchasing decisions (T = 1.637 p = 0.102). Findings: This study highlights that viral marketing plays an important role in increasing purchase decisions, while celebrity endorsement and halal labeling have a negative impact on purchase decisions, with no significant direct influence on purchase decisions. Novelty: This research provides new empirical insights into the interaction between celebrity endorsement, viral marketing, and halal labeling on purchasing decisions. Originality: This study is original because of its focus on the role of purchasing decisions in the context of celebrity endorsement, viral marketing, and halal labeling. Conclusion: Celebrity endorsements, viral marketing, and halal labels are key to understanding customer purchasing decisions. Paper Type: Research Article.